Gichtbehandlung beeinflusst Lebensqualität und Produktivität (Aktuelle Rheumatologie, 2017)
Wood R et al. Patients with Gout Treated with Conventional Urate-lowering Therapy: Association with Disease Control, Health-related Quality of Life, and Work Productivity